2017
DOI: 10.1111/cen.13447
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and tolerability of taste‐masked hydrocortisone granules in neonates, infants and children under 6 years of age with adrenal insufficiency

Abstract: SummaryObjectives: There is no licensed, dose-appropriate formulation of hydrocortisone for children with adrenal insufficiency (AI) and patients rely on compounded adult medication. The aim of this study was to evaluate the absorption, palatability and safety of Infacort ® , an immediate-release, granule formulation of hydrocortisone with taste masking. Study design:Single site with satellites attended by a "flying" doctor from investigator site. Open-label, single-dose study in three consecutive child cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Six of the 12 children in the oldest cohort responded to an adjusted palatability questionnaire, with ≥50% subjects reporting that the taste, feel in mouth and ease of swallowing were very good and that they were likely to take the medicine again. No serious adverse events were seen throughout the study, and the adverse events seen were mild (most common reported were diarrhoea, vomiting and rash) and not attributed to investigational product (6).…”
Section: Background and Overview Of The Marketmentioning
confidence: 93%
See 3 more Smart Citations
“…Six of the 12 children in the oldest cohort responded to an adjusted palatability questionnaire, with ≥50% subjects reporting that the taste, feel in mouth and ease of swallowing were very good and that they were likely to take the medicine again. No serious adverse events were seen throughout the study, and the adverse events seen were mild (most common reported were diarrhoea, vomiting and rash) and not attributed to investigational product (6).…”
Section: Background and Overview Of The Marketmentioning
confidence: 93%
“…The challenge for paediatric patients and their health care providers is that hydrocortisone is only licensed in 10 and 20mg tablet doses in the European Union and children require much smaller doses (of the order of 1-2mg three times daily in infants), and are unable to swallow tablets designed for adults (5). Current clinical practice is for pharmacists to compound hydrocortisone either by tablet crushing or using hydrocortisone base to produce a powder or special solutions of hydrocortisone or in some countries, such as the United Kingdom, for parents to crush tablets (6)(7)(8). All such practice is unlicensed and not subject to the level of regulation and quality control of licensed drug manufacture where Good Manufacturing Practice (GMP) regulations mean that every aspect of manufacturing must be described, controlled and regularly assessed with a quality management system in place at each step.…”
Section: Background and Overview Of The Marketmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be administered with food, liquids or as dry granules directly onto the child's tongue. It is available in 0.5, 1, 2 and 5 mg doses (69). Infacort® may represent a valid option for precise dosing in paediatric patients with AI.…”
Section: Paediatric Formulationsmentioning
confidence: 99%